Stamp2 Protects From Maladaptive Structural Remodeling and Systolic Dysfunction in Post-Ischemic Hearts by Attenuating Neutrophil Activation - Mollenhauer, Martin; Bokredenghel, Senai; Geißen, Simon; Klinke, Anna; Morstadt, Tobias; Torun, Merve; Strauch, Sabrina; Schumacher, Wibke; Maass, Martina; Konradi, Jürgen; Peters, Vera B. M.; Berghausen, Eva; et al. (Frontiers in Immunology, 2021)
The six-transmembrane protein of prostate 2 (Stamp2) acts as an anti-inflammatory protein in macrophages by protecting from overt inflammatory signaling and Stamp2 deficiency accelerates atherosclerosis in mice. Herein, we describe an unexpected role of Stamp2 in polymorphonuclear neutrophils (PMN) and characterize Stamp2’s protective effects in myocardial ischemic injury. In a murine model of ischemia and reperfusion (I/R), echocardiography and histological analyses revealed a pronounced impairment of cardiac function in hearts of Stamp2-deficient- (Stamp2-/-) mice as compared to wild-type (WT) animals. This difference was driven by aggravated cardiac fibrosis, as augmented fibroblast-to-myofibroblast transdifferentiation was observed which was mediated by activation of the redox-sensitive p38 mitogen-activated protein kinase (p38 MAPK). Furthermore, we observed increased production of reactive oxygen species (ROS) in Stamp2-/- hearts after I/R, which is the likely cause for p38 MAPK activation. Although myocardial macrophage numbers were not affected by Stamp2 deficiency after I/R, augmented myocardial infiltration by polymorphonuclear neutrophils (PMN) was observed, which coincided with enhanced myeloperoxidase (MPO) plasma levels. Primary PMN isolated from Stamp2-/- animals exhibited a proinflammatory phenotype characterized by enhanced nuclear factor (NF)-κB activity and MPO secretion. To prove the critical role of PMN for the observed phenotype, antibody-mediated PMN depletion was performed in Stamp2-/- mice which led to full recovery of left ventricular function and prevented adverse structural remodeling after I/R. These data indicate a novel role of Stamp2 as an anti-inflammatory regulator of PMN and fibroblast-to-myofibroblast transdifferentiation in myocardial I/R injury.